Differential phosphorylation regulates the shear stress‐induced polar activity of Rho‐specific guanine nucleotide dissociation inhibitor α. Issue 10 (31st January 2020) - Xie, Fei; Shao, Shuai; Zhang, Baohong; Deng, Sha; Ur Rehman Aziz, Aziz; Liao, Xiaoling; Liu, Bo
Abstract: The activity of Rho‐specific guanine nucleotide dissociation inhibitor α (RhoGDIα) is regulated by its own phosphorylation at different amino acid sites. These phosphorylation sites may have a crucial role in local Rho GTPases activation during cell migration. This paper is designed to explore the influence of phosphorylation on shear stress‐induced spatial RhoGDIα activation. Based on the fluorescence resonance energy transfer biosensor sl‐RhoGDIα, which was constructed to test the RhoGDIα activity in living cells, new RhoGDIα phosphomimetic mutation (sl‐S101E/S174E, sl‐Y156E, sl‐S101E, sl‐S174E) and phosphorylation‐deficient mutation (sl‐S101A/S174A, sl‐Y156A, sl‐S101A, sl‐S174A) biosensors were designed to test their effects on RhoGDIα activation upon shear stress application in human umbilical vein endothelial cells (HUVECs). The results showed lower RhoGDIα activity at the downstream of HUVECs (the region from the edge of the nucleus to the edge of the cell along with the flow). The overall decrease in RhoGDIα activity was inhibited by Y156A‐mutant, whereas the polarized RhoGDIα and Rac1 activity were blocked by S101A/S174A mutant. It is concluded that the Tyr156 phosphorylation mainly mediates shear stress‐induced overall RhoGDIα activity, while Ser101/Ser174 phosphorylation mediates its polarization. This study demonstrates that differential phosphorylation of RhoGDIα regulates shear stress‐induced spatial RhoGDIα activation, which could be a potential target to control cell migration. Abstract : Rho‐specific guanine nucleotide dissociation inhibitor α (RhoGDIα Y156) phosphorylation mediates overall RhoGDIα activity. RhoGDIα S101/S174 phosphorylation influences its polarization and the downstream of Rac1 activation upon shear stress application.